Analisis Faktor-Faktor yang Mempengaruhi Penerimaan Opini Audit Going Concern Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia: Penelitian - Cindy Cantika; Dwi Saraswati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The research analysis aims to analyze the factors influencing the acceptance of going-concern audit opinions in manufacturing companies listed on the Indonesia Stock Exchange. This study used multiple linear regression analysis. The sample size for this study was 19 companies. Primary data collection was conducted using a questionnaire. The results showed that profitability had a significance value of 0.032 <0.05, or less than 0.05. Therefore, it can be concluded that the relationship between profitability and going-concern audit opinions, or the first hypothesis (H1) is accepted. Solvency had a significance value of 0.027 <0.05, or less than 0.05. Therefore, it can be concluded that the relationship between solvency and going-concern audit opinions, or the second hypothesis (H2) is accepted. Liquidity had a significance value of 0.225 >0.05, or greater than 0.05. Therefore, it can be concluded that the relationship between liquidity and going-concern audit opinions does not affect the going-concern audit opinion, or the third hypothesis (H3) is rejected. The significant value of the profitability test in the simultaneous test means that the profitability value is 0.026 < 0.05. Profitability, solvency, and liquidity influence the going-concern audit opinion, or the first hypothesis (H4) is accepted.